Dynamic of Carbon and Nitrogen Concentrations in the Decomposition of Leaf Litter of Subtropical Crops in Southeastern Spain - Rodríguez Pleguezuelo, Carmen Rocío (2017)
Litter decomposition is one on the main routes of energy consume in an ecosystem and one of the principal roles in nutrient cycling. On the other side, in the last decades, subtropical crops have expanded importantly along the coast of Granada (SE Spain). To evaluate the cycles a bag technique experiment was carried out by using mango leaves (Mangifera indica L.), cherimolia (Annona cherimola Mill.), avocat (Persea americana Mill.) and loquat (Eriobotrya japonica L.). The main objective of this work was monitoring the dynamic of litter decomposition of these crops leaves and the evolution of their contents in carbon and nitrogen in a Mediterranean subtropical climate context. Bags were buried and recovered at certain time periodically to evaluate carbon and nitrogen concentration as well as mass losses. The results of this study showed that farmers could benefit of the knowledge of nutrient dynamics in litter decomposition to improve soil organic matter in the long term and to incorporate nitrogen. In this sense, loquat and mango showed the highest nitrogen accumulation and as a consequence these types of litters could be used as organic soil amendments in the long term. Contrarily, cherimolia accumulated higher carbon amounts than the rest of the studied crops.